The Effect of Perceived Usefulness, Trust and Visual Information toward Attitude and Purchase Intention - Moh Farid Najib; Vika Gustyana Mulyani; Alexandre Desausa Guteres (Journal of Marketing Innovation (JMI), 2021)
Bandung is one of culinary cities in Indonesia that continues to show the growth of restaurant businesses. It provides intense competition for the culinary industries to keep the businesses alive. The consumer trend itself changes to how-to learning company through the choice of article, for example the use of Instagram. This study thus aims to identify the influence of Instagram food blogger elements namely perceived usefulness, trust, and visual information on consumer buying attitudes and their purchase intentions. To test the proposed model, this study applies variance-based structural equations Partial Least Squares (PLS) modeling with 200 Instagram food blogger who are recommended by the readers in Bandung, Indonesia as the samples. The results show all variables have positive effects on attitudes and purchase intention. In contrary, perceived usefulness does not give significant effect on purchase intention. As a follow-up on the results of the study, the managerial implication of these findings is discussed.